A preliminary review of horse-rider reaction times in the equestrian population - Williams, J.; Barnett, K. (International Journal of Performance Analysis in Sport, 2013)
Reaction time is defined as the time between the onset of a sensory stimulus and the subsequent behavioral response. This study aimed to investigate reaction times of members of the horse riding population, testing for variables in subject lifestyles which affect reaction time. Fifty-three subjects completed questionnaires including personal details and information on their normal lifestyle and equestrian involvement. Subjects' reaction times were measured using a computerised game. No significant difference was found between the reaction times for the right or left hands. An increase in reaction time was associated with an increase in age (r=0.744, P0.05). The study identified that as subject age (years) increased, reaction time increased and, surprisingly, that the population did not appear to exhibit hand dominance proposed to be due to striving for a balanced rein contact. To fully assess the effect of sleep, stimulants and experience/competition level on reaction time, further investigation is required. However, identification of factors that impact on rider reaction times will allow these to be considered during equestrian human athlete development to enhance equine performance and reduce injuries to horse and rider.